POLITICAL PARTIES BETWEEN ELECTORAL INTERESTS AND PUBLIC REPRESENTATION: A CRITICAL ANALYSIS OF LOCAL DEMOCRACY IN INDONESIA (Proceeding of SINERGY, 2026)
Political parties are a key pillar of representative democracy, but in local democratic practices in Indonesia, their role tends to be diminished by the dominance of electoral interests. This article aims to critically analyze how the electoral orientation of political parties influences the quality of public representation, transactional political practices, and elite power relations in the context of regional head elections (Pilkada). This research uses a qualitative approach using literature review and document analysis, including Pilkada regulations and previous empirical studies. The analytical framework is based on the theories of procedural and substantive democracy (Dahl), the institutionalization of political parties (Panebianco), and the theory of political oligarchy (Winters). The results show that high political costs encourage the practice of political dowries, candidate dependence on sponsors, and the strengthening of transactional politics, ultimately weakening the accountability of regional heads after their election. Furthermore, the dominance of local elites and the lack of political competition indicate that political parties function more as arenas for elite negotiation than as institutions of public representation. These findings highlight the gap between procedural and substantive democracy in local democracy. This article concludes that strengthening local democracy requires institutional reform of political parties to reorient them toward representing the public interest.